Predicting Success of Catheter Drainage in Infected Necrotizing Pancreatitis. Issue 4 (April 2016) - Hollemans, Robbert A.; Bollen, Thomas L.; van Brunschot, Sandra; Bakker, Olaf J.; Ali, Usama Ahmed; van Goor, Harry; Boermeester, Marja A.; Gooszen, Hein G.; Besselink, Marc G.; van Santvoort, Hjalmar C.
Abstract : Introduction: At least 30% of patients with infected necrotizing pancreatitis are successfully treated with catheter drainage alone. It is currently not possible to predict which patients also need necrosectomy. We evaluated predictive factors for successful catheter drainage. Methods: This was a post hoc analysis of 130 prospectively included patients undergoing catheter drainage for (suspected) infected necrotizing pancreatitis. Using logistic regression, we evaluated the association between success of catheter drainage (ie, survival without necrosectomy) and 22 factors regarding demographics, disease severity (eg, Acute Physiology And Chronic Health Evaluation II score, organ failure), and morphologic characteristics on computed tomography (eg, percentage of necrosis). Results: Catheter drainage was performed percutaneously in 113 patients and endoscopically in 17 patients. Infected necrosis was confirmed in 116 patients (89%). Catheter drainage was successful in 45 patients (35%). In multivariable regression, the following factors were associated with a reduced chance of success: male sex [odds ratio (OR) = 0.27; 95% confidence interval (CI): 0.09–0.55; P <0.01), multiple organ failure (OR = 0.15; 95% CI: 0.04–0.62; P < 0.01), percentage of pancreatic necrosis (<30%/30%–50%/>50%: OR = 0.54; 95% CI: 0.30–0.96; P = 0.03), and heterogeneous collection (OR = 0.21; 95% CI: 0.06–0.67; P < 0.01). A prediction model incorporating these factors demonstrated an area under the receiver operating characteristic curve of 0.76. A prognostic nomogram yielded success probability of catheter drainage from 2% to 91%. Conclusions: Male sex, multiple organ failure, increasing percentage of pancreatic necrosis and heterogeneity of the collection are negative predictors for success of catheter drainage in infected necrotizing pancreatitis. The constructed nomogram can guide prognostication in clinical practice and risk stratification in clinical studies.